The Utilization of Ordinary National Educational Test Score - Thanarachataphoom, Thananun (Journal of Education Studies, Chulalongkorn University, 2020)
The National Institute of Educational Testing Services (Public Organization) was allocated a budget from Thailand’s government to administer the Ordinary National Educational Test (O-NET) for students who study under the Basic Education Core Curriculum B.E. 2551 (A.D.2008). The O-NET is held to test the knowledge and thinking ability and assess academic proficiency of Grade 6, 9 and 12 students according to the Basic Education Core Curriculum B.E 2551 (A.D. 2008). There are 6 types of utilization of the ONET score: 1) to be one of graduation criteria 2) to be one of secondary students admission criteria 3) to be one of university admission criteria 4) to be an indicator or a goal of educational development 5) to develop learning and enhance students’ achievement and 6) serve as data for educational research.